An investigation into the perceptions of school counsellors in relation to providing counselling for students with special needs in Saudi Arabia schools - Aloteabi, Youssef Hathal (2018)
The purpose of this study is to gain an in-depth understanding of the perceptions of school counsellors in Saudi Arabia with regard to the provision of counselling for students with special educational needs (SEN) and to determine the contribution of counsellors to the development of such students in the context of mainstream secondary boys’ schools in Saudi Arabia. Accordingly, the study employs a mixed-methods approach to explore the perceptions of school counsellors in the country. Quantitative insights are obtained from 138 counsellors working in secondary boys’ schools using a questionnaire designed for the study. Subsequently, qualitative insights are obtained from 12 counsellors who are currently working with students with SEN and 12 counsellors who have never worked with students with SEN using semi-structured interviews. The quantitative data is statistically analysed, whereas the qualitative data is analysed using interpretative phenomenological analysis (IPA). Overall, it is found that the qualitative and quantitative findings support each other and indicate that the provision of school counselling in Saudi Arabia for students with SEN requires attention. Salient findings include the existence of systemic issues such as the absence of minimum standards for counsellor recruitment, irregular recruitment practices, and inadequate dissemination of information associated with the purpose, role and function of school counsellors. Moreover, it is found that inadequate training provision and supervision and support mechanisms for counsellors exist, along with a lack of collaboration between departments of the Ministry of Education. Additionally, the findings indicate that the sociocultural environment of Saudi Arabia prohibitively influences the provision of school counselling services, in general, as the Islamic collectivist values with regard to family, hierarchy, secrecy, shame and stigma, are revealed to hinder the provision of counselling in schools. Moreover, counsellors find their work in the schools hampered by their involvement in non-counselling tasks, negative perceptions with regard to the usefulness of their role, lack of awareness about the needs of students with SEN. It is evident that the counselling profession in Saudi Arabia is yet to obtain full professional recognition and status as the country does not have a statutory body to provide support and guidance regarding the professional and ethical practice of counsellors, and to engage with the Ministry on behalf of counsellors. The findings of the study contribute to understanding the current status of the provision of school counselling services to students with SEN in boys’ secondary schools in Saudi Arabia. Suggestions based on the study’s findings are offered to the Ministry of Education in Saudi Arabia, to counsellors working with children with SEN, and to the administration and personnel in schools. Suggestions for future research are also discussed.